VALIDITAS BAHAN AJAR MATTERPLAY UNTUK MEREDUKSI MISKONSEPSI SISWA SEKOLAH DASAR - Muhammad Yazid Fatkhul Mujib; Wahyu Kurniawati (Dharmas Education Journal (DE_Journal), 2026)
Learning in Natural and Social Sciences (IPAS) in the Merdeka Curriculum emphasizes meaningful learning through active student involvement to build scientific conceptual understanding. However, in practice, elementary school students still experience misconceptions, particularly on the topic of states of matter and their changes. This study aims to determine the validity of the MatterPlay interactive teaching material developed to reduce misconceptions in IPAS learning. This research employed the Research and Development (R&D) method by adapting the 4D development model proposed by Thiagarajan, which consists of the define, design, development, and disseminate stages; however, this study was conducted only up to the development stage. The validation process involved two validators, namely a media expert and a subject matter expert, using a four-point Likert scale assessment instrument. The results showed that MatterPlay obtained a validity score of 94% from the media expert and 100% from the material expert, both categorized as very valid. Therefore, MatterPlay is considered valid and feasible to be used in IPAS learning in elementary schools.